2021
DOI: 10.3390/app11104669
|View full text |Cite
|
Sign up to set email alerts
|

Injuries and Pain Associated with Goalkeeping in Football—Review of the Literature

Abstract: Knowledge and research about football goalkeeper (GK) injuries are scarce, which prevents the development of evidence-based injury prevention programs. Fortunately, progress is evident in injury prevention strategies in outfield football players. However, a GK fulfills a unique role, and an injured GK can substantially impact a team. Thus, there is a need to clarify and summarize current knowledge concerning football goalkeeper pain and injuries. This narrative review aims to present the best-evidence synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 87 publications
(131 reference statements)
0
6
0
Order By: Relevance
“…However, there is a lack of data specifically focusing on injuries among adolescent goalkeepers. 1 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is a lack of data specifically focusing on injuries among adolescent goalkeepers. 1 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have indicated that goalkeepers may experience higher injury rates in their upper limbs, particularly in their fingers, hands, and wrists, while conflicting findings have been presented by other studies. 2 , 29 , 30 Marchessault et al 31 mentioned that hand and wrist injuries comprise 3-9% of all sports injuries. The scaphoid is the most affected bone, especially after axial load and hyperextension trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these areas are particularly at risk of creating plantless spots due to goalkeeper interventions (Fig. 10 ), which result in the body falling to the ground 71 , 72 and damaging the surface (requiring overseeding, which is not always possible due to the ongoing league season). As can be seen from the obtained results, it had a lower tendency to deteriorate quality, along with turf age in areas characterized by a higher functional value (middle area, playing area) in the first evaluation periods.…”
Section: Discussionmentioning
confidence: 99%
“…Regular exercise has a significant impact on children's overweight levels. According to Muracki et al (2021), goalkeepers sometimes have a higher fat percentage than players in other positions. Maintaining body weight is crucial for agility in movement, speed, and the body's reaction to the arrival of the opponent and the ball.…”
Section: Hypothesis Testingmentioning
confidence: 99%